Unheard Voices in Adaptive Classrooms Exploring Emotional Narratives of Children with Special Needs - Maisura, Maisura; Putra, Muakhir Syah (Education Achievement: Journal of Science and Research, 2025)
In the past decade, the global attention to inclusive education has driven structural transformations in learning systems, including in adaptive classrooms. However, even though physical and curricular access is expanding, the emotional voice of children with special needs (CWSN) is still often ignored in the empirical discourse of education. This qualitative research aims to explore and elevate the emotional narrative of CWSN in the context of an adaptive inclusive class. Using a phenomenological approach, data were collected through non-invasive observational techniques combined with journals of teacher reflection and children's creative expression (such as free images and stories) from 12 children aged 7–11 years in three inclusive primary schools. The results show that although adaptive classes have provided structural accommodation, the response to the emotional needs of CWSN is still inadequate. Some of the key themes that emerge in children's narratives include feelings of silence, fragile attachment, and the occasional happiness—suggesting that true inclusion cannot be achieved through physical adjustment alone, but rather requires deeper affective and relational engagement. This research makes an important contribution to the inclusive education literature by emphasizing the importance of emotional literacy, recognition of children's voices, and affectively responsive pedagogy as an integral part of inclusive classroom design. The implications of this study confirm the need for teacher training that places the emotional aspect at the center of a participatory culture and inclusive learning for all learners.